Association of poor mental health and skin cancer development: a cross-sectional study of adults in the United States. Issue 6 (November 2020) - Tkachenko, Elizabeth; Singer, Sean; Mostaghimi, Arash; Hartman, Rebecca I.
Abstract : The relationship between mental health and skin cancer is poorly characterized. This cross-sectional study used 2016 Behavioral Risk Factor Surveillance System data to evaluate the association between mental health problems and skin cancer development. Multivariate logistic regression analyses were performed to calculate adjusted odds ratio (aOR) for skin cancer development by mental health problems, adjusting for potentially confounding demographic and lifestyle factors. Odds of skin cancer were significantly higher in those with mental health problems problems [aOR 1.24, 95% confidence interval (CI) 1.17–1.31, P  < 0.001]; this finding remained in sensitivity analysis adjusting for sunburn history (aOR 1.34, 95% CI 1.09–1.63, P  = 0.004). Our findings reveal an association between poor mental health and increased skin cancer prevalence. The direction of this association is unclear. Distress of a skin cancer diagnosis may promote mental health problems, while, conversely, mental health problems may biologically potentiate skin cancer or be associated with risk factors like indoor tanning. Nevertheless, we demonstrate an elevated prevalence of mental health problems in patients with skin cancer.